A Systematic Review and Meta-Analysis of Robot-Assisted Mitral Valve Repair. Issue 6 (November 2022) - Fatehi Hassanabad, Ali; Nagase, Fernanda N. I.; Basha, Ameen M.; Hammal, Fadi; Menon, Devidas; Kent, William D. T.; Ali, Imtiaz S.; Nagendran, Jeevan; Stafinski, Tania
Objective: Robot-assisted surgery is a minimally invasive approach for repairing the mitral valve. This study aimed to assess its safety and clinical efficacy when compared with conventional sternotomy, partial sternotomy, and right minithoracotomy. Methods: A systematic review of peer-reviewed studies comparing robot-assisted mitral valve repair with conventional sternotomy, partial sternotomy, and right minithoracotomy was conducted following Cochrane Collaboration guidelines. Meta-analyses were performed where possible. Results: The search strategy yielded 15 primary studies, of which 12 compared robot-assisted with conventional sternotomy, 2 compared robot-assisted with partial sternotomy, and 6 compared robot-assisted with right minithoracotomy. The overall quality of evidence was low, and there was a lack of data on long-term outcomes. Individual studies and pooled data demonstrated that robotic procedures were comparable to conventional sternotomy and other minimally invasive approaches with respect to the rates of stroke, renal failure, reoperation for bleeding, and mortality. Robot-assisted mitral valve repair was superior to conventional sternotomy with reduced atrial fibrillation, intensive care unit and hospital stay, pain, time to return to normal activities, and physical functioning at 1 year. However, robot-assisted mitral valve repair had longer cardiopulmonary, aortic cross-clamp, and procedure times compared with all other surgical approaches. Conclusions: Based on current evidence, robot-assisted mitral valve repair is comparable to other approaches for safety and early postoperative outcomes, despite being associated with longer operative times. Ideally, future studies will be randomized controlled trials that compare between robot-assisted surgery, conventional surgery, and other minimally surgery approaches focusing on hard clinical outcomes and patient-reported outcomes.